The Railway children - Nesbit, Edith (Lahore : Maqbool Books, 2000)
The Railway Children is a classic children's novel that follows the lives of three siblings$1 (BRoberta (Bobbie), Peter, and Phyllis$1 (Bwho move to a countryside home near a railway after their father is mysteriously taken away. Adjusting to their new life, they embark on adventures and form bonds with railway workers and travelers. Through their innocence and compassion, the children help solve a series of problems, including reuniting their family. The story explores themes of resilience, kindness, and the power of family love in the face of hardship.s